EXPLORING MULTICULTURALISM IMPLEMENTATION TO FOSTER DIVERSITY AMONG ELEMENTARY SCHOOL STUDENTS - Sandi Budiana; Novi Anoegrajekti; Muhammad Kamal bin Abdul Hakim (Indonesian Journal of Learning and Instruction, 2022)
This research focuses on analyzing the actual state of implementing multiculturalism and identifying strategies to improve its effectiveness in elementary school students from an early age. The study employs a qualitative method and collects data from elementary school teachers and principals through in-depth interviews, documentation studies, and observation. The data obtained is then analyzed through data reduction, data presentation, and drawing conclusions. The study reveals that the majority of elementary school teachers view the implementation of multiculturalism as highly important, while a smaller portion considers it important. Teachers emphasize the importance of multiculturalism in maintaining social harmony, preventing conflicts among residents, fostering awareness of diversity within the country, and upholding national unity and integrity. A significant number of teachers express strong support for the development of teaching materials that integrate multiculturalism. However, the current implementation of multiculturalism lacks a systematic approach in planning, implementation, and evaluation. To enhance the effectiveness of implementing multiculturalism in elementary school students, teachers can employ various strategies.Keywords: diversity; learning material; multiculturalism; qualitative approach.